2017
DOI: 10.2527/tas2017.0025
|View full text |Cite
|
Sign up to set email alerts
|

Development of highly digestible animal feed from lignocellulosic biomass Part 2: Oxidative lime pretreatment (OLP) and shock treatment of corn stover1

Abstract: Oxidative lime pretreatment (OLP) increases lignocellulose digestibility by removing lignin and hemicellulose acetyl content. Digestibility is improved further by adding mechanical shock treatment, which subjects aqueous slurry of biomass to an explosive pressure pulse. Shock treatment mechanically disrupts the microscopic structure while maintaining the macroscopic integrity of the biomass particle. This study determined the effectiveness of these pretreatments to enhance the ruminant digestibility of corn st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
(13 reference statements)
1
10
0
Order By: Relevance
“…This is a contrast to Ca(OH) 2 pretreatment, in which previous studies showed oxygen improves digestibility. 7,20,31,35,40 This low effect of oxygen on NaOH pretreatment was observed with and without the inclusion of hydrolyzed filtrate (Figure 12). These results show that in NaOH pretreatments, pressurized oxygen does not benefit enzymatic digestibility.…”
Section: Oxygen Pressurementioning
confidence: 93%
See 4 more Smart Citations
“…This is a contrast to Ca(OH) 2 pretreatment, in which previous studies showed oxygen improves digestibility. 7,20,31,35,40 This low effect of oxygen on NaOH pretreatment was observed with and without the inclusion of hydrolyzed filtrate (Figure 12). These results show that in NaOH pretreatments, pressurized oxygen does not benefit enzymatic digestibility.…”
Section: Oxygen Pressurementioning
confidence: 93%
“…According to Falls et al, shock treatment alone causes a slight increase in cellulose crystallinity and has a negative impact on enzymatic digestibility. 20,25 However, previous studies have shown that combining shock treatment with oxidative lime pretreatment greatly increases biomass digestibility. 20,21,25 Falls et al hypothesized that even though shock slightly increases crystallinity, this negative effect is countered from the disruption of the lignin/hemicellulose matrix surrounding cellulose, providing greater access for enzymes.…”
Section: Redefining the Control Experimentsmentioning
confidence: 99%
See 3 more Smart Citations